ANALISIS STRATEGI PENGEMBANGAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (Studi Kasus pada Hasil Olahan Perikanan di Gorontalo) - Bumulo, Frahmawati; Prajawati, Maretha Ika (IQTISHODUNA, 2016)
Some districts have reached the shoreline approximately 75 KM certainly have huge marine potentialand have the potential that has not been managed optimally and thus still require government attention andserious investors to handle. This study uses secondary data and qualitative methods with direct interviewswith fishermen and institutions associated with using SWOT Analysis and Test Litmust Test.The resultsshowed that the SWOT performed using 11 strategic issues, namely repair of structures and infrastructurescoastal and marine areas in accordance with the development potential and capacity of the environment,improving education and skills of coastal fishing communities, developing models and capture technology,setting the boundary zone of preservation , increase surveillance activities, support groups of fishermen inpartnering efforts, increase the production of processed products of fisheries, improving engineering capabilityutilization and management of coastal areas and the sea.This research concluded that by applying the rightstrategy and the cooperation of various parties, both institutions, financial institutions, private sector andcoastal fishing communities can raise the productivity of coastal fishing communities themselves that areexpected to improve the local revenue.